Functional amyloids in Pseudomonas aeruginosa may be involved in the sequestration of the quorum sensing molecules HHQ and PQS under high shear conditions. - Sia, Wan Rong. (2013)
Pseudomonas aeruginosa is an opportunistic pathogen that causes chronic infections in cystic fibrosis patients. In the airways of the lungs, fluids are flowing at inconsistent rate and this could dilute concentrations of signalling molecules and nutrients that are important to the pathogen. These signalling molecules regulate the formation of biofilm and production of virulence factors, hence playing a role in its pathogenicity. We hypothesize that P.aeruginosa express amyloid-like fimbrae, Fap, to bind to these molecules to prevent their loss into the environment. The binding affinities of Fap to Quorum Sensing (QS) molecules were investigated using Surface Plasmon Reasonance and a bioreporter assay. Results from the investigations revealed that Fap binds to QS molecules at high affinities and was able to retain them under high shear force. Therefore, we propose that Fap has a functional role in sequestering QS molecules under high shear conditions.